2019
DOI: 10.1186/s13014-019-1216-1
|View full text |Cite
|
Sign up to set email alerts
|

Early stage non-small cell lung cancer treated with pencil beam scanning particle therapy: retrospective analysis of early results on safety and efficacy

Abstract: BackgroundTo evaluate the safety and efficacy of particle therapy (PT) using pencil beam scanning (PBS) technique for early stage non-small cell lung cancer (NSCLC).MethodsFrom 08/2014 to 03/2018, 31 consecutive patients with sum of the longest diameters of primary tumor and hilar lymph node < 5 cm, N0–1, M0 NSCLC treated with PT were retrospectively analyzed. Gating/active breathing control techniques were used to control tumor motion in 20 and 7 patients. PBS-based proton radiotherapy (PRT) or carbon ion rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…Patients in both arms received concurrent chemotherapy consisting of weekly paclitaxel/ carboplatin with or without cetuximab. Unexpectedly, overall survival was worse in the high dose arm (median OS 29 months versus 20 months) 31 . The results of another doseescalation study, the PET-boost trial (NCT01024829), are upcoming and may provide further clarification in the dose-escalation matter.…”
Section: Treatment Of Locally Advanced Non-small Cell Lung Cancermentioning
confidence: 93%
See 4 more Smart Citations
“…Patients in both arms received concurrent chemotherapy consisting of weekly paclitaxel/ carboplatin with or without cetuximab. Unexpectedly, overall survival was worse in the high dose arm (median OS 29 months versus 20 months) 31 . The results of another doseescalation study, the PET-boost trial (NCT01024829), are upcoming and may provide further clarification in the dose-escalation matter.…”
Section: Treatment Of Locally Advanced Non-small Cell Lung Cancermentioning
confidence: 93%
“…Regional recurrence free survival was comparable (87% for SABR versus 95% for surgery at 3 years; p=0.18) in the final propensity-matched comparison of 56 patients matched on age, tumour size, comorbidity score, forced expiratory volume in the first second of expiration and tumour location. Overall survival (OS) seemed to be better for the surgical patients: the authors report a 3-year OS of 52% for SABR versus 68% for surgery (p=0.05) 31 . Another study reported on the outcomes of SABR or wedge resection for stage I NSCLC in patients ineligible for anatomic lobectomy 32 .…”
Section: Incidence Of Hilar/mediastinal Lymph Node Metastases Followimentioning
confidence: 99%
See 3 more Smart Citations